Sequential Mixed Cultures: From Syngas to Malic Acid - Oswald, Florian; Dörsam, Stefan; Veith, Nicolas; Zwick, Michaela; Neumann, Anke; Ochsenreither, Katrin; Syldatk, Christoph (Frontiers in Microbiology, 2016)
Synthesis gas (syngas) fermentation using acetogenic bacteria is an approach for production of bulk chemicals like acetate, ethanol, butanol or 2,3-butandiol avoiding the fuel vs. food debate by using carbon monoxide, carbon dioxide and hydrogen from gasification of biomass or industrial waste gases. Suffering from energetic limitations, yields of C4-molecules produced by syngas fermentation are quite low compared with ABE fermentation using sugars as a substrate. On the other hand, fungal production of malic acid has high yields of product per gram metabolized substrate but is currently limited to sugar containing substrates. In this study , it was possible to show that Aspergilus oryzae is able to produce malic acid using acetate as sole carbon source which is a main product of acetogenic syngas fermentation. Bioreactor cultivations were conducted in 2.5 L stirred tank reactors. During the syngas fermentation part of the sequential mixed culture, Clostridium ljungdahlii was grown in modified Tanner medium and sparged with 20 mL/min of artificial syngas mimicking a composition of clean syngas from entrained bed gasification of straw (32.5 vol-% CO, 32.5 vol-% H2, 16 vol-% CO2 and 19 vol-% N2) using a microsparger. Syngas consumption was monitored via automated gas chromatographic measurement of the off-gas. For the fungal fermentation part gas sparging was switched to 0.6 L/min of air and a standard sparger. Ammonia content of medium for syngas fermentation was reduced to 0.33 g/L NH4Cl to meet the requirements for fungal production of dicarboxylic acids. Malic acid production performance of A. oryzae in organic acid production medium and syngas medium with acetate as sole carbon source was verified and gave YP/S values of 0.28 and 0.37 respectively. Growth and acetate formation of C. ljungdahlii during syngas fermentation were not affected by the reduced ammonia content and 66 % of the consumed syngas was converted to acetate. The overall conversion of CO and H2 into malic acid was calculated to be 3.5 g malic acid per mol of consumed syngas or 0.22 g malic acid per gram of syngas.